Reduction of admissions for urgent and elective pacemaker implant during the COVID-19 outbreak in Northern Italy. Issue 1 (January 2022) - Dell'Era, Gabriele; Colombo, Crizia; Forleo, Giovanni B.; Curnis, Antonio; Marcantoni, Lina; Racheli, Marco; Sartori, Paolo; Notarstefano, Pasquale; De Salvia, Alberto; Guerra, Federico; Ziacchi, Matteo; Tondo, Claudio; et al.
Abstract : Aims: The coronavirus disease-19 (COVID-19) outbreak has been recently associated with lower hospitalization rates for acute coronary syndromes. Aim of the study was to investigate whether a similar behaviour is observed in admissions for urgent pacemaker implant. Methods: This retrospective study included 1315 patients from 18 hospitals in Northern Italy with a high number of COVID-19 cases. Hospitalization rates for urgent pacemaker implant were compared between the following periods: 20 February to 20 April 2020 (case period); from 1 January to 19 February 2020 (intra-year control period); from 20 February to 20 April 2019 (inter-year control period). Results: The incidence rate of urgent implants was 5.0/day in the case period, 6.0/day in the intra-year control period and 5.8/day in the inter-year control period. Incidence rate in the case period was significantly lower than both the intra-year [incidence rate ratio (IRR): 0.81, 95% CI 0.67–0.99, P = 0.040] and inter-year control periods (IRR: 0.79, 95% CI 0.66–0.95, P = 0.012); this reduction was highest after the national lockdown (IRR 0.68, 95% CI 0.52–0.91, P = 0.009). The prevalence of residents in rural areas undergoing urgent pacemaker implant was lower in the case period (36%) than in both the intra-year (47%, P = 0.03) and inter-year control periods (51%, P = 0.002). Elective pacemaker implants also decreased in the case period, with the incidence rate here being 3.5/day vs. 6.4/day in the intra-year (−45%) and 6.9/day in the inter-year period (−49%). Conclusion: Despite severe clinical patterns, the COVID-19 outbreak has negatively affected the population presentation to Emergency Departments for bradyarrhythmias requiring urgent pacemaker implant in Northern Italy. This mainly occurred after the national lockdown and concerned patients living in rural areas.